2022
DOI: 10.1097/md.0000000000031750
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid adenoma presenting as chronic pancreatitis: A case report and literature review

Abstract: Background: Most patients with parathyroid adenomas are asymptomatic and rarely present with chronic pancreatitis (CP). Several studies have reported a positive association between primary hyperparathyroidism (PHPT) and pancreatitis. Parathyroidectomy is the definitive treatment for PHPT. IV bisphosphonates can be considered the drug of choice for bridge to surgery.Methods: We reported a 57-year-old female patient was admitted to the emergency room with left upper quadrant abdominal pain and a diagnosis of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Summarizing, in addition to the five previously mentioned cases of pregnancy primary hyperparathyroidism [37][38][39]41,42] and three reports of a parathyroid carcinoma [47][48][49], another seventeen articles introduced one patient per case study, except for two papers with two subjects (a total of nineteen individuals). Four children (aged between 9 and 14 years; an average age of 12; female-to-male ratio of three to one) and fifteen adults (aged between 31 and 81 years; mean age of 51.6 years; female-to-male ratio of two to one) were reported within the last five years in the field of hypercalcemia-derivate pancreatitis in patients with parathyroid NETs (N = 27 individuals) [18,21,22,25,34,35,[53][54][55][56][57][58][59][60][61][62][63] (Table 4). From a cross-disciplinary perspective, the synchronous identification of pancreatitis and primary hyperparathyroidism requires the dual management of pancreatic involvement and hypercalcemia in the sense of rapid calcium lowering, and, when clinically stable, a definite cure of primary hyperparathyroidism should be provided by parathyroidectomy.…”
Section: Pancreatitis and Pth-dependent Hypercalcemiamentioning
confidence: 99%
See 3 more Smart Citations
“…Summarizing, in addition to the five previously mentioned cases of pregnancy primary hyperparathyroidism [37][38][39]41,42] and three reports of a parathyroid carcinoma [47][48][49], another seventeen articles introduced one patient per case study, except for two papers with two subjects (a total of nineteen individuals). Four children (aged between 9 and 14 years; an average age of 12; female-to-male ratio of three to one) and fifteen adults (aged between 31 and 81 years; mean age of 51.6 years; female-to-male ratio of two to one) were reported within the last five years in the field of hypercalcemia-derivate pancreatitis in patients with parathyroid NETs (N = 27 individuals) [18,21,22,25,34,35,[53][54][55][56][57][58][59][60][61][62][63] (Table 4). From a cross-disciplinary perspective, the synchronous identification of pancreatitis and primary hyperparathyroidism requires the dual management of pancreatic involvement and hypercalcemia in the sense of rapid calcium lowering, and, when clinically stable, a definite cure of primary hyperparathyroidism should be provided by parathyroidectomy.…”
Section: Pancreatitis and Pth-dependent Hypercalcemiamentioning
confidence: 99%
“…Usually, an acute episode of pancreatitis is not recognized as being triggered by primary hyperparathyroidism, and patients continue to have two or three episodes until adequate identification of the underlying parathyroid condition [ 22 , 54 ]. For instance, Mehta et al [ 55 ] reported the case of an adult lady who suffered from three episodes of acute pancreatitis during six months in the absence of alcohol consumption or gallstones until parathyroid-related hypercalcemia was incriminated as the pancreatic disease [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Paratiroid bezlerinin en sık saptanan benign tümörlerinden birisi olan paratiroid adenomları PHPT %80'inden daha fazlasından sorumludur. 4 PHPT tedavisi, görüntüleme yöntemlerindeki gelişmeler ve prospektif çalışmaların sonuçlarının ortaya konması ile son 20-30 yılda kapsamlı bir değişim geçirmiştir. Güncel kılavuzlar serum PTH düzeyleri yüksek olan ve hiperkalsemiye bağlı komplikasyonların ortaya çıktığı hastalarda paratiroidektomi yapılmasını önermektedir.…”
Section: Introductionunclassified